A 3D sensor based deflection correction algorithm for belt layer - Su Ming; Fan Wenqiang; Xiao Dong (Dianzi Jishu Yingyong)
In order to solve the problem that the center position of the belt layer is offset during transmission, a 3D sensor based belt layer deviation correction algorithm is proposed in this paper. Firstly, the contour data collected by 3D sensor is preprocessed to make the data smoother. Secondly, in the process of correcting deviation, the belt layer is divided into three regions: upper, middle and lower regions, the upper and lower regions adopt fixed edge, and the middle region adopts fixed center. The real-time correction is carried out by calculating different positions in three different regions. Finally, through MATLAB simulation, the correction accuracy of the algorithm can reach within 1 mm, which is better than the traditional unilateral correction accuracy and correction stability.